Balancing a Rotary Double Inverted Pendulum using Two-loops Adaptive Controller based on Dynamic Inversion Technique - Shah, M.H.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
Balancing control of a double inverted pendulum is a great challenge as it is an unstable and non-linear system that requires fast control reaction. In this paper, a dynamic inversion controller is proposed for balancing control of a rotary double inverted pendulum system. The controller consists of two loops where the outer loop is responsible for generating desired position command while the inner loop takes the command to produce the actual control action. The robustness of the controller is added by the introduction of the sliding surface vector function. The effectiveness of the proposed controller is investigated through numerical simulations with two other types of controllers that are also tested for comparison purposes. The results prove that the proposed controller capable of balancing the rotary double inverted pendulum under the influence of disturbances, while comparisons with Sliding Mode Controller (SMC) and Linear Quadratic Regulator (LQR) in various scenarios suggested that the proposed controller was the most consistent controller as opposed to the other two. Â© 2021 IEEE.